Sluggish Cognitive Tempo and Daytime Sleepiness Mediate Relationships Between Sleep and Academic Performance. Issue 8 (October 2021) - O'Hare, Kirstie; White, Naomi; Harding, Rebecca; Galland, Barbara; Sellbom, Martin; Shine, Ben; Schaughency, Elizabeth
ABSTRACT: Objective: Sleep difficulties, daytime sleepiness, and sluggish cognitive tempo (SCT) are associated with impairments in academic performance. SCT refers to symptoms of sluggishness, tiredness/lethargy, and slowed thinking/processing, but despite symptom overlap with sleepiness, research examining interrelations of SCT with sleep and daytime sleepiness is limited. The aims of this study were to evaluate the relationship between SCT and daytime sleepiness and to examine pathways between sleep, daytime sleepiness, SCT, and academic performance. Method: Participants were a community sample of 1628 parents/caregivers of children aged between 6 and 10 years who completed questionnaires about their child's behavior, sleep, and academic performance. Confirmatory factor analysis was used to examine whether SCT was distinct from daytime sleepiness. Then, structural equation modeling was used to examine direct and indirect pathways between sleep (sleep-disordered breathing [SDB] symptoms, sleep duration, and latency), daytime sleepiness, SCT, and academic performance in reading, writing, and math. Results: SCT and daytime sleepiness were distinct but moderately correlated ( r = 0.33, p ⩽ 0.001). Sleep, in particular SDB symptoms, predicted increased SCT and daytime sleepiness. SCT was directly and negatively associated with all domains of academic performance, daytime sleepiness was associated with poorer reading performance, and longer sleep duration was directly associated with poorer math performance. SCT and, to a lesser extent, daytime sleepiness mediated effects of sleep on academic performance. Conclusion: SCT symptoms are important for understanding how sleep difficulties affect academic performance in children. Sleep, daytime sleepiness, and SCT are interrelated but distinct factors that affect children's academic performance. Abstract : This article has supplementary material on the web site: www.jdbp.org.